Offene-Welt-Strukturen - Bonner, Marc (Büchner-Verlag, 2023)
What role do algorithms play in the construction of images and the representation of the world and weather in computer games? How does the design of rooms, levels and topographies influence the decisions and behavior of the players? Is Brutalism the first genuine architectural style of computer games? What is the importance of landscape gardens and national parks in structuring game worlds? How is nature represented in times of climate change? Particularly in the last 20 years, digital game worlds are adapting features of the physical real world more meticulously than ever before. Through elaborate production processes and complex visualization strategies, the adaptation to the rest of our everyday world is always created in dependence on game mechanics and worldliness. As can be seen at the latest in the example of open-world games, the adoption of certain worldviews and visual traditions leads to ideological implications that go far beyond the narrative conventions transferred from other media formats that have been the focus of research so far. With his theory of architecture as a medial hinge, Marc Bonner reveals that digital game worlds exhibit media-specific properties that were previously out of reach and awaited exploration. By interweaving concepts from media studies, game studies, philosophy, architectural theory, human geography, landscape theory, and art history, among others, Bonner develops a transdisciplinary theoretical model and, using the analytical methods developed from it, makes it possible for the first time to understand and name the complex structure of today's computer games - from indie games to AAA open worlds. With »Offene-Welt-Strukturen« (»Open World Structures«) the architectonics of digital game worlds becomes comprehensively accessible.